Optimization of cereal productivity and physiological performance under desert conditions: varying irrigation, salinity and planting density levels - García-Caparros, Pedro; Al-Dakheel, Abdullah J.; Serret, Maria D.; Araus, Jose L. (Frontiers in Plant Science, 2025)
Adequate irrigation with low-quality water, aligned with the specific water requirements of crops, will be critical for the future establishment of cereal crops on marginally fertile soils. This approach is essential to support global food security. To identify suitable cereal species and genotypes for these challenging conditions with the aim of optimizing yield and resilience, three different cereal species were tested under sandy soil conditions at the experimental fields of ICBA (Dubai, UAE). The experimental design employed a factorial combination split-plot arrangement including five primary factors: crop species (barley, triticale and finger millet), genotypes (3 in barley, 3 in triticale and 2 in finger millet), salinity levels (2 and 10 dS m-1), irrigation levels (100%, 150%, and 200% ETo), and planting densities (30 and 50 cm of spacing between rows). Agronomic parameters (e.g. plant height, grain yield, total plant dry weight and harvest index) and physiological parameters [Normalized Difference Vegetation Index (NDVI) readings, together with nitrogen and carbon concentration isotopic composition, chlorophyll, flavonoids, and anthocyanins concentrations in flag leaves and the Nitrogen Balance Index (NBI)] exhibited distinct genotypic responses across the species investigated. Regarding grain yield, salt stress did not impact barley and finger millet, whereas triticale experienced a reduction of nearly one third of its yield. Increased irrigation led to higher grain yields only in barley, while increased planting density significantly improved grain yield across all species examined demonstrating its potential as a simple agronomic intervention. Physiological responses highlighted reduced nitrogen isotope composition under both salt stress and higher planting density in all species. Nevertheless, the response to irrigation varied among species exhibiting significant negative correlations with aerial plant dry matter. In contrast, carbon isotope composition did not display a clear pattern in any of the species studied under different agronomic treatments. These results underscore the importance of selecting salt and drought tolerant species and optimizing planting density to maximize productivity on marginal soils. Future research should focus on refining irrigation strategies and identification of high-performing genotypes to improve cereal cultivation in arid regions, contributing to global food security.